Efforts of Religious Education Teachers in Diagnosing Students' Learning Difficulties - Syahid, Syafira Irma; Fitri, Rika; Ernayenti, Ernayenti; Rahmita, Rahmita; Busmayaril, Busmayaril; Defrianto, Defrianto; Mutathahirin, Mutathahirin (Al-kayyis: Journal of Islamic Education, 2025)
Islamic Religious Education is something very valuable for a person; it cannot be denied that through Islamic Religious Education we can distinguish a person's character. Through Islamic Religious Education, a person can become obedient and devout. However, there are several efforts that must be made before achieving maximum results, namely the efforts of an Islamic Religious Education teacher in diagnosing or identifying students' learning difficulties. This study aims to identify the learning difficulties students face during the learning process, which the teacher then describes. This study employs a qualitative approach with a descriptive method, with data sources derived from observations, interviews, and documentation. The research findings indicate that teachers' efforts in diagnosing learning difficulties are already being implemented effectively, but their execution is not yet optimal. This is evident first in the fact that Islamic Religious Education teachers have not yet maximized classroom observations to observe students' deviant behavior during lessons. the implication is that the efforts of Islamic Education teachers in diagnosing learning difficulties through interviews with parents have been going well, but they are still not maximizing their efforts to interview parents to find out the family conditions that are causing problems for students in their learning. Therefore, the approach taken by teachers should not be limited to telephone calls without visiting the homes of students who are experiencing learning difficulties. Teachers should visit the homes of students who are experiencing learning difficulties in order to find out what problems the students are facing.